Continuous subcutaneous insulin infusion versus multiple daily injection regimens in children and young people at diagnosis of type 1 diabetes: pragmatic randomised controlled trial and economic evaluation. (3rd April 2019) - Blair, Joanne C; McKay, Andrew; Ridyard, Colin; Thornborough, Keith; Bedson, Emma; Peak, Matthew; Didi, Mohammed; Annan, Francesca; Gregory, John W; Hughes, Dyfrig A; Gamble, Carrol
Abstract: Objective: To compare the efficacy, safety, and cost utility of continuous subcutaneous insulin infusion (CSII) with multiple daily injection (MDI) regimens during the first year following diagnosis of type 1 diabetes in children and young people. Design: Pragmatic, multicentre, open label, parallel group, randomised controlled trial and economic evaluation. Setting: 15 paediatric National Health Service (NHS) diabetes services in England and Wales. The study opened to recruitment in May 2011 and closed in January 2017. Participants: Patients aged between 7 months and 15 years, with a new diagnosis of type 1 diabetes were eligible to participate. Patients who had a sibling with the disease, and those who took drug treatments or had additional diagnoses that could have affected glycaemic control were ineligible. Interventions: Participants were randomised, stratified by age and treating centre, to start treatment with CSII or MDI within 14 days of diagnosis. Starting doses of aspart (CSII and MDI) and glargine or detemir (MDI) were calculated according to weight and age, and titrated according to blood glucose measurements and according to local clinical practice. Main outcome measures: Primary outcome was glycaemic control (as measured by glycated haemoglobin; HbA1c) at 12 months. Secondary outcomes were percentage of patients in each treatment arm with HbA1c within the national target range, incidence of severe hypoglycaemia and diabetic ketoacidosis, change in height and body mass index (as measured by standard deviation scores), insulin requirements (units/kg/day), partial remission rate (insulin dose adjusted HbA1c <9), paediatric quality of life inventory score, and cost utility based on the incremental cost per quality adjusted life year (QALY) gained from an NHS costing perspective. Results: 294 participants were randomised and 293 included in intention to treat analyses (CSI, n=144; MDI, n=149). At 12 months, mean HbA1c was comparable with clinically unimportant differences between CSII and MDI participants (60.9 mmol/mol v 58.5 mmol/mol, mean difference 2.4 mmol/mol (95% confidence interval −0.4 to 5.3), P=0.09). Achievement of HbA1c lower than 58 mmol/mol was low among the two groups (66/143 (46%) CSII participants v 78/142 (55%) MDI participants; relative risk 0.84 (95% confidence interval 0.67 to 1.06)). Incidence of severe hypoglycaemia and diabetic ketoacidosis were low in both groups. Fifty four non-serious and 14 serious adverse events were reported during CSII treatment, and 17 non-serious and eight serious adverse events during MDI treatment. Parents (but not children) reported superior PedsQL scores for those patients treated with CSII compared to those treated with MDI. CSII was more expensive than MDI by £1863 (€2179; 2474; 95% confidence interval £1620 to £2137) per patient, with no additional QALY gains (difference −0.006 (95% confidence interval −0.031 to 0.018)). Conclusion: During the first year following type 1 diabetes diagnosis, no clinical benefit of CSII over MDI was identified in children and young people in the UK setting, and treatment with either regimen was suboptimal in achieving HbA1c thresholds. CSII was not cost effective. Trial registration: Current Controlled Trials ISRCTN29255275 ; European Clinical Trials Database 2010-023792-25.